2021
DOI: 10.1186/s12931-021-01758-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-life cost-effectiveness of benralizumab in patients with severe asthma

Abstract: Background Availability of clinically effective and cost-effective treatments for severe asthma would be beneficial to patients and national healthcare systems. The aim of this study was to evaluate clinical outcomes and healthcare expenditure after incorporating benralizumab into the standard treatment of refractory eosinophilic asthma. Methods This was a cross-sectional multicentre study of consecutive patients with refractory eosinophilic asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…In this regard, we have seen that some RWE studies are beginning to provide interesting evidence. [99][100][101][102][103][104][105][106][107][108] In the context of national and international registries and large databases, RWE studies can go beyond one of their most significant limitations, which is the low number of patients examined. 117,118 Big data obtained from networks and registers will also allow us to define alternative treatment schemes and dosages, but it is currently necessary to refer to those available.…”
Section: Complementary Results Between Clinical Trials and Real-life ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, we have seen that some RWE studies are beginning to provide interesting evidence. [99][100][101][102][103][104][105][106][107][108] In the context of national and international registries and large databases, RWE studies can go beyond one of their most significant limitations, which is the low number of patients examined. 117,118 Big data obtained from networks and registers will also allow us to define alternative treatment schemes and dosages, but it is currently necessary to refer to those available.…”
Section: Complementary Results Between Clinical Trials and Real-life ...mentioning
confidence: 99%
“…Menzies-Gow et al 67 : The PONENTE study, conducted to establish an OCS tapering protocol given the great efficacy of benralizumab, was an open-label multicentre trial involving patients with severe steroid-dependent asthma. The primary endpoint was to determine how quickly and safely the OCS Padilla-Galo et al 103 : A Spanish multicentre cross-sectional study in patients with SEA treated with benralizumab for at least 12 months showed that this biologic may also be a cost-effective agent based on the pharmacoeconomic parameters analysed (direct costs and incremental cost-effectiveness ratio).…”
Section: Dupilumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Лечение генно-инженерными биологическими препаратами позволяет не только улучшить течение БА и предупредить ее обострения, но и существенно снизить эффективные дозы глюкокортикостероидов или даже отменить их [52]. Результаты ряда фармакоэкономических исследований показали и экономическую целесообразность таргетной противоастматической терапии [53,54].…”
Section: генно-инженерные биологические препараты в лечении баunclassified
“…The challenge of inhalers with a high level of intelligence seems to be a significant topic inspired by prior efforts. The conventional technologies have drawbacks like a restricted range, propellants, and freon effects that are chilly [10].…”
Section: Introductionmentioning
confidence: 99%